A Framework Proposal for Quality and Safety Measurement in Gynecologic Emergency Care. Issue 5 (November 2020) - Fauconnier, Arnaud; Provot, Johan; Le Creff, Isabelle; Boulkedid, Rym; Vendittelli, Françoise; Doret-Dion, Muriel; Sroussi, Jérémy; Giraudet, Géraldine; Jacobs, Romain; Bourret, Antoine; Bauville, Estelle; Carvalho, Solenn; et al.
Abstract : OBJECTIVE: To define and assess the prevalence of potentially life-threatening gynecologic emergencies among women presenting for acute pelvic pain for the purpose of developing measures to audit quality of care in emergency departments. METHODS: We conducted a mixed-methods multicenter study at gynecologic emergency departments in France and Belgium. A modified Delphi procedure was first conducted in 2014 among health care professionals to define relevant combinations of potentially life-threatening conditions and near misses in the field of gynecologic emergency care. A prospective case–cohort study in the spring of 2015 then assessed the prevalence of these potentially life-threatening emergencies and near misses among women of reproductive age presenting for acute pelvic pain. Women in the case group were identified at 21 participating centers. The control group consisted of a sample of women hospitalized for acute pelvic pain not caused by a potentially life-threatening condition and a 10% random sample of outpatients. RESULTS: Eight gynecologic emergencies and 17 criteria for near misses were identified using the Delphi procedure. Among the 3, 825 women who presented for acute pelvic pain, 130 (3%) were considered to have a potentially life-threatening condition. The most common diagnoses were ectopic pregnancies with severe bleeding (n=54; 42%), complex pelvic inflammatory disease (n=30; 23%), adnexal torsion (n=20; 15%), hemorrhagic miscarriage (n=15; 12%), and severe appendicitis (n=6; 5%). The control group comprised 225 hospitalized women and 381 outpatients. Diagnostic errors occurred more frequently among women with potentially life-threatening emergencies than among either hospitalized (odds ratio [OR] 1.7, 95% CI 1.1–2.7) or outpatient (OR 14.7, 95% CI 8.1–26.8) women in the control group. Of the women with potentially life-threatening conditions, 26 met near-miss criteria compared with six with not potentially life-threatening conditions (OR 25.6, 95% CI 10.9–70.7). CONCLUSIONS: Potentially life-threatening gynecologic emergencies are high-risk conditions that may serve as a useful framework to improve quality and safety in emergency care. Abstract : Potentially life-threatening gynecologic emergencies are high-risk conditions that may serve as a useful framework to improve quality and safety in emergency care.